Facial attendance system technology using Microsoft Cognitive Services. (28th May 2021) - Mayan, J. Albert; Karthikeyan, S.; Chandak, Nikhil; Mundhra, Bharat; Padmavathy, J.
Artificial intelligence is a necessity in the current times as it makes processes more economical and affordable in the long run. It also frees humans from performing banal tasks day in and day out. Once a process is automated the only check that is to be performed is whether it is turned on or not. Artificial intelligence is an automated process which is not prone to errors and even if an error is identified rectification is easy and can be applied system-wide without any delay. Taking attendance is a mundane but necessary task in many academic institutions. In this paper, an alternate and more efficient method of taking attendance is proposed that uses face recognition and IoT technology with the help of cognitive services. Facial attendance system technology is a combination of front end technology like angular, IoT device like Raspberry Pi and its peripherals, back end technology with Node.js framework, cloud technology like Firebase and Microsoft Cognitive Services. The main objective of using Microsoft Cognitive Services is for accuracy and fast development of the system. The process from face detection to face recognition is done in minimal span of time with the help of cognitive services.